Effects of fire disturbance on bird communities and species of mountain Serrano Forest of Central Argentina - Dardanelli, Sebastián (2014)
In central Argentina, Serrano forest has a long history of fire disturbance; however, the impact of fire on avifauna remains unknown. We compared the avian?habitat relationships in forest patches with low, moderate, and high fire regimes using a community-level (species richness, abundance, ordination and guilds) and species-level (indicator species analysis) approach. In patches under each fire condition, we recorded bird community composition,richness and abundance, and different vegetation structure variables. The site under high-severity fire regime was structurally poor and had been converted from original forest to dense grassland. There, diversity of bird communitywas low, retaining approximately 30 % of the species present in the least impacted site. Avian assemblage was dominated by generalist and open area birds.Guilds were underrepresented, showing an important reduction of foliage granivorous, nectarivorous, omnivores, and foliage and bark insectivorous, and absence of flycatchers. Moreover, low abundance of forest understory, midstory, and canopy species and of birds belonging to open and closed nesting guilds was detected. By contrast, under low and moderate-severity fire regimes highest bird diversity as well as highest representativeness of most guilds was observed. Forest bird species were strongly associated with low fire disturbance, whereas moderate fire disturbance was characterized by the presence of forest andgeneralist species. Given the critical conservation status of Serrano forest in Cordoba, Argentina, habitat restoration and protection of forest relicts could be suitable measures to promote avifauna preservation.